FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA SEKTOR INFRASTRUKTUR - Deyana Maharani Riantho; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research aims to empirically prove the effect of Profitability, Firm Size, Sales Growth, and Liquidity on Firm Value in registered infrastructure sector companies on IDX for the 2019-2021 period. Data samples were taken using purposive sampling method. After outlier test, 83 valid data were obtained from 40 companies. The results of this research are based on multiple linear regression testing, which uses the SPSS Statistics Version26 for data processing. The results showed that profitability had a significant positive effect on firm value, firm size had a significant negative effect on firm value, while sales growth and liquidity had no significant effect on firm value.